Communicating war in Mali, 2012: On-offline networked political agency in times of conflict. (1st June 2015) - Bruijn, Mirjam de; Pelckmans, Lotte; Sangare, Boukary
The Arab Spring raised high expectations for political freedom, especially for situations in which the rapid development of ICT intersects with political oppression and rebellion, as was the case in Mali, West Africa. In 2012 the country's northern part fell into the hands of 'rebels' and jihadists were on the rise. This article tries to understand the development of political agency in relation to the unprecedented access to new ICT of the Fulani nomads and urbanites in the Mopti region (Hayre), who engage increasingly with new actors and networks present in the war zone: 'rebels' and jihadists; the diaspora from that region; and the journalistic and academic communities who visit the region. We argue that political agency is emerging in the relation between (newly appearing) information networks in both the on- and off-line worlds. These networked societies are embedded in cultural and social historical specificities of the Sudan-Sahel zone in conflict.